Core Components of Quality Education in the Quality Management Support System: A Systematic Review (SAIM Journal of Social Science and Technology, 2025)
Purpose: This systematic review synthesizes research on core components of quality education—curriculum, teaching, learners, leadership, resources, and parental engagement—within the Quality Management Support System (QMSS) framework.Methodology: Following PRISMA guidelines, 50 peer-reviewed studies and policy reports from 2000 to 2024 were thematically analyzed, sourced from Scopus and Google Scholar using keywords related to educational quality.Findings: Quality education requires a coherent curriculum aligned with standards, skilled and reflective teachers using learner-centered practices, motivated learners supported by families, strong leadership, equitable resources, and active family-school partnerships. These elements align with UNESCO’s SDG4 and UNICEF’s Education Quality Framework.Conclusions: Fragmented efforts focusing on individual components are insufficient. A QMSS approach integrating all elements through continuous monitoring and stakeholder feedback is essential for systemic educational improvement.Originality: This review uniquely integrates core educational quality components within the QMSS framework, emphasizing their interdependence and alignment with global standards, promoting a holistic rather than isolated approach.